A novel surface treatment for bamboo flour and its effect on the dimensional stability and mechanical properties of high density polyethylene/bamboo flour composites. (20th October 2018) - Zhang, Weipeng; Yao, Xu; Khanal, Santosh; Xu, Shiai
Graphical abstract: Highlights: Hydrophobic bamboo flour was prepared by melt blending method. AKD modified WPCs show high water resistance and low swelling ratio. AKD modified WPCs show better mechanical properties than alkali treated composites. Abstract: In this study, bamboo flour (BF) was chemically modified using alkyl ketene dimer (AKD) or alkali treatment for the preparation of high-density polyethylene/bamboo flour (HDPE/BF) composites with or without compatibilizer maleic anhydride grafted high-density polyethylene (HDPE- g -MAH). The modified BF was characterized by Fourier transformation infrared (FTIR) spectroscopy and contact angle measurement, and the mechanical properties, morphology and water resistance of the HDPE/BF composites were investigated and compared. The results show that highly hydrophobic BF can be obtained by a simple procedure using a common paper sizing agent AKD. AKD can react with the hydroxyl groups in cellulose to form β-keto ester. The combination of AKD treatment and addition of HDPE- g -MAH is more effective in improving the mechanical properties of HDPE/BF composites than using them alone. The impact strength, flexural strength and modulus of HDPE/A-BF/MAH composite are increased by 100.0%, 197.1% and 61.8% compared with that of HDPE/U-BF composites, and the water absorption and thickness swelling are decreased by 87.7% and 87.4% after immersion in water for one week, respectively. These results indicate that HDPE/BF composites with good mechanical properties and high water resistance can be obtained by AKD treatment.